Sex differences in solid pseudopapillary neoplasm of the pancreas: A population‐based study - Jiali Wu; Yize Mao; Yiquan Jiang; Yunda Song; Ping Yu; Shuxin Sun; Shengping Li (Cancer Medicine, 2020)
Abstract Objective Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare tumor. This study aims to examine the clinicopathological features and surgical treatments of SPN and compare the clinical behavior and prognosis between men and women with SPN. Methods We collected the population data of patients with SPN diagnosed between 2004 and 2017 from the SEER database. The Kaplan‐Meier method was used to analyze overall survival (OS) and disease‐specific survival (DSS), and log‐rank tests were used to evaluate the differences between subgroups. Univariate and multivariate Cox regression analyses were performed to screen out prognostic risk factors of SPN. Results A total of 378 patients with SPN were included, with 246 (65.1%) female patients. 1‐, 3‐, and 5‐year overall survival rates were 98.9%, 95.7%, and 93.7%, respectively. Survival analysis revealed that regardless of stage, patients with SPN who underwent surgical interventions still had a significantly better prognosis than those without surgical interventions (P < .001). The patients with lymphatic dissection had a significantly better prognosis than those without lymphatic dissection (P < .001). Moreover, compared with female patients, male patients had significantly poorer OS and DSS (P < .001). Female SPN showed a bimodal age‐frequency distribution with early‐onset incidence at 28 years and late‐onset peak incidence at 62 years, while male SPN presented a unimodal distribution with peak incidence at approximately age 64 years. In female patients, the tumor size in premenopausal females (<65 years old) was significantly larger than that in postmenopausal females (≥65 years old) (P < .001). Clinicopathological characteristic profiles were different not only between male SPN and premenopausal female SPN but also between premenopausal and postmenopausal female SPN. Conclusion SPN presents indolent behavior and predominantly occurs in young women. Regardless of stage, surgical intervention is recommended. Moreover, our study is the first large enough study to demonstrate sex‐related discrepancies in SPN. Thus, different treatment strategies should be designed for patients of different sexes at different ages and hormone therapy is a promising approach for SPN.